(untitled) (Swiss Medical Weekly, 2011)
OBJECTIVE: To provide population-based, gestational age (GA) stratified incidence of mortality and morbidities. METHODS:Population-based prospective observational study of infants born between 23 0/7 and 31 6/7 weeks GA in the years 2000–2004 in all Swiss neonatal intensive care units. Outcomes measured were: mortality, severe intraventricular haemorrhage (IVH), periventricular leukomalacia (PVL), necrotizing enterocolitis (NEC), moderate/severe bronchopulmonary dysplasia (BPD) and free of major complications. RESULTS: Mortality was 19% of 3083 infants. Mortality (95% CI) decreased from 95% (88%, 99%) at 23 weeks to 3% (2%, 5%) at 31 weeks. Short-term survival free of major complications was 66% (65%, 68%) overall and increased from 2%(0%, 9%) to 89% (87%, 92%). Rate of IVH was 8% (7%, 9%), PVL 2% (2%, 3%), NEC 3% (3%, 4%) and BPD 11% (10%, 12%). Males had more IVH than females (9% vs. 6%). Antenatal steroids were associated with lower mortality (11% vs. 18%) and IVH (5% vs. 12%). Odds of free of major complications (OR, 95%CI) were positive for female gender 1.2 (1.0, 1.5), steroids 1.3 (1.1, 1.5), multiple gestation 1.3 (1.0, 1.6), not small for gestational age 2.7 (2.0, 3.5), and each additional week of GA 1.6 (1.5, 1.7). CONCLUSION: Mortality and incidence of morbidities known to influence outcome show a weekly decline with increasing gestational age, except for PVL. Gestational age stratified data are a key component for prenatal counselling.